The related factors of phlebitis among low birth weight infants in perinatology ward - Yuningsih, Risna (Pediatr Rep, 2020)
Peripheral intravenous line placement might lead to some risks and complications in low birth weight (LBW) infants including phlebitis, which shows varying percentages. This study aimed to analyze the causative factors of phlebitis among LBW infants in a perinatology ward. A total of 106 LBW infants who selected using a consecutive sampling technique were analyzed with cross-sectional method. Data were collected when LBW infants started receiving infusions until the infusion was stopped under certain conditions, using the Infusion Nurses Society (INS) phlebitis scale and the Neonatal Infant Pain Scale (NIPS) as the instrument. The variables related to phlebitis under bivariate analysis included the clinical experience of intravenous insertion, infusion pumps, site of insertion, neonatal birth weight, and the administration of total parenteral nutrition. The most significant risk factor of phlebitis was the nurses’ clinical experience of intravenous insertion (< 2 years). Therefore, the results of this study can be considered to improve the quality of nursing care in perinatology ward.